2021
DOI: 10.1186/s13036-021-00275-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the efficiency of synergistic photocatalysis on penicillin G biodegradation by whole cell Paracoccus sp

Abstract: Background The Paracoccus sp. strain isolated from sludge was identified and evaluated for catalytic activity in the degradation of penicillin G. Results High degradation efficiency and synergistic catalytic effects of the whole cell and visible light without additional catalysts were observed. The key factors influencing the degradation and kinetics of penicillin G were investigated. The results showed the phenylacetic acid, which was produced dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Based on previous studies, it was shown that Paracoccus-KDSPL-02 accelerates the rate of degradation of penicillin G in the presence of light [8-10] . However, the molecular mechanism by which it accelerates the degradation of penicillin G is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous studies, it was shown that Paracoccus-KDSPL-02 accelerates the rate of degradation of penicillin G in the presence of light [8-10] . However, the molecular mechanism by which it accelerates the degradation of penicillin G is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…There are various degradation methods for penicillin G, such as physical degradation, chemical degradation, and biodegradation, among which biodegradation has attracted much attention because of its green, environmental, friendly, and efficient advantages [6,7] . Isolation of a strain of Paracoccus-KDSPL-02 from the sludge of a pharmaceutical factory, which is highly efficient for the degradation of penicillin G [8] . The strain has a wide range of degradation capabilities and can biodegrade a variety of compounds [11] .…”
Section: Introductionmentioning
confidence: 99%